2017
DOI: 10.1155/2017/4097973
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Challenges in the Diagnosis and Treatment of Temporal Bone Osteomyelitis

Abstract: Temporal bone osteomyelitis is a serious life-threatening condition—a quick and proper diagnosis is needed to start treatment and reduce morbidity and mortality. Changing trends of the disease make a differential diagnosis difficult. To emphasize the importance of a clinical suspicion of this dangerous condition, our experience with three difficult cases is presented. The diagnosis was based on clinical symptoms, otoscopic findings, and findings on computed tomography or magnetic resonance imaging. Neoplasm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The partial thrombosis of sigmoid sinuses seen on MRI is probably due to the retrograde progression of thrombus from IJV to sigmoid sinus, as a result of sluggish or hampered blood flow. The MOE is also known to cause jugular foramen syndrome with IJV thrombosis ( Low and Lhu, 2018 ; Kornilenko et al., 2017 ). However, jugular foremen was also an unlikely site of involvement in our case since the cranial nerves X and XI were normal clinically, and the jugular foremen was not involved radiologically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The partial thrombosis of sigmoid sinuses seen on MRI is probably due to the retrograde progression of thrombus from IJV to sigmoid sinus, as a result of sluggish or hampered blood flow. The MOE is also known to cause jugular foramen syndrome with IJV thrombosis ( Low and Lhu, 2018 ; Kornilenko et al., 2017 ). However, jugular foremen was also an unlikely site of involvement in our case since the cranial nerves X and XI were normal clinically, and the jugular foremen was not involved radiologically.…”
Section: Discussionmentioning
confidence: 99%
“…The IJV thrombosis in MOE by itself has been reported sparsely and very rarely has this been attributed to parapharyngeal space involvement ( Kornilenko et al., 2017 ; Low and Lhu, 2018 ; Kornilenko et al., 2017 ; Davidoss et al., 2015 ; Turan et al., 2014 ). On the other hand, though many authors have reported a non-predictable spread of the MOE to involve non-contagious sites belonging to separate compartments causing VI, VII, IX, X, XI, XII nerve palsies in various combinations very rarely these deficits have been thought to be due to parapharyngeal space involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality rate of skull base osteomyelitis is 33 per cent, reaching up to 80 per cent in patients with cranial nerve involvement. 48 The management for patients with skull base osteomyelitis is different from that for patients with necrotising otitis externa without skull base involvement. Surgery may be used in the treatment of skull base osteomyelitis, especially when there is cranial nerve involvement.…”
Section: Introductionmentioning
confidence: 99%